Global Business in Local Culture The Impact of Embedded Multinational Enterprises - Aerni, Philipp (SpringerBriefs in Economics, 2018)
This book examines the impact of multinational enterprises (MNEs) on local economies, and presents selected case studies of MNEs operating in low income countries. By balancing external social and environmental costs against its corresponding benefits, the book demonstrates that MNEs can have a positive net-impact on local development if they build up social capital by embedding themselves in local economies and engaging responsibly with local stakeholders. By doing so MNEs contribute to inclusive growth, a central pillar of the UN Sustainable Development Goals. In this context, the book challenges popular narratives in civil society and academia that frame foreign direct investment (FDI) merely as a threat to human rights and sustainable development. Moreover, it offers practical guidance for globally operating businesses seeking to establish progressive Corporate Social Responsibility (CSR) strategies of their own.